Jewish Thought Adrift Max Wiener (1882-1950) - Schine, Robert S. (Brown Judaic Studies, 2020)
Robert Schine's intellectual biography of Max Wiener profiles a liberal German-Jewish thinker who turned toward Zionism as the only natural future for Judaism. Schine puts Wiener's thought into conversation with those of his German contemporaries (both Jewish and Christian) while also resuscitating Wiener's thought as a resource for contemporary theologians.